The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1086/605338
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Severe Rotavirus Diarrhea in Indonesia

Abstract: Globally, rotavirus is the leading cause of diarrhea-related hospitalizations and deaths among young children, but the burden of rotavirus disease in Indonesia is poorly documented. From January through December 2006, we conducted prospective surveillance (inpatient and outpatient) among children aged <5 years at 6 hospitals in 6 provinces of Indonesia, using standardized methodology. Of 2240 enrolled children hospitalized for diarrhea, 1345 (60%) were rotavirus positive. Of 176 children enrolled in outpatient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
67
2
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(82 citation statements)
references
References 24 publications
7
67
2
6
Order By: Relevance
“…In our study, vomiting was associated with rotavirus positivity (Table 4), which aligns with the findings of other studies (20,28). Those studies also reported that rotavirus-positive patients were less likely to have bloody diarrhoea (20,28), in agreement with our study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, vomiting was associated with rotavirus positivity (Table 4), which aligns with the findings of other studies (20,28). Those studies also reported that rotavirus-positive patients were less likely to have bloody diarrhoea (20,28), in agreement with our study.…”
Section: Discussionsupporting
confidence: 93%
“…Putnam et al (19), who conducted a study in Medan, Makassar, Jakarta, Yogyakarta, Surabaya, Bali and Nusa Tenggara, found that 748 of 1,660 (45.1%) children under five years of age suffered from diarrhoea due to rotavirus. Moreover, Soenarto et al (20), who conducted a study of children under five years of age in Yogyakarta, Jakarta, Bandung, Mataram, Denpasar and Palembang in 2006, showed that 60% of the 2,240 children studied suffered from diarrhoea due to rotavirus. These findings support the need for continuous surveillance of the disease in various locations.…”
Section: From February To August 2009 104mentioning
confidence: 99%
“…Our study inclusion age were between 1 and 18 year-old to reduce the bias of fever and gastrointestinal issues due to other disease, which is common in infants such as Rotavirus. Children age less than two years were prompt to higher risk of rotavirus-positive diarrhea with incidence of 1185 of 1345 (88%) patients during study period [16]. Moreover we also believe that infants under one year-old in our country are still being breastfed and receive home-prepared meal, whereas there is a higher possibility that infants above 1 year-old would receive meals prepared from outside home with higher dietary diversity, which impose children to higher risk for typhoid fever infection.…”
Section: Discussionmentioning
confidence: 97%
“…Penggunaan antibiotik sebagai terapi pada kasus diare anak perlu mendapat perhatian khusus dengan mempertimbangkan patogen penyebab infeksi pada sebagian besar kasus diare adalah non-bakteri. Beberapa bukti penelitian terpublikasi menunjukkan penyebab terbanyak diare akut pada anak di berbagai daerah di dunia, termasuk Indonesia, adalah rotavirus 1, 4,8,7 .…”
Section: Hasil Dan Pembahasanunclassified